2021
DOI: 10.1016/j.preteyeres.2020.100883
|View full text |Cite
|
Sign up to set email alerts
|

TCF4-mediated Fuchs endothelial corneal dystrophy: Insights into a common trinucleotide repeat-associated disease

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a common cause for heritable visual loss in the elderly. Since the first description of an association between FECD and common polymorphisms situated within the transcription factor 4 ( TCF4 ) gene, genetic and molecular studies have implicated an intronic CTG trinucleotide repeat (CTG18.1) expansion as a causal variant in the majority of FECD patients. To date, several non-mutually exclusive mechanisms have been proposed that drive and/or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 242 publications
0
82
0
Order By: Relevance
“…In the unrelated cohort, we also identified CTG18.1 expansion, defined as ≥40 repeats, in 7.7% (95% CI, 4%–11%) of 235 control subjects (≥50 years old), consistent with previous reports in US and European cohorts, 33 but higher than that in studies of Asian cohorts. 12 As a group, our CTG18.1exp+ control subjects did not have repeat lengths significantly different than CTG18.1exp+ FECD patients, so we cannot conclude that CTG18.1exp+ controls have relatively shorter expansions. In fact, one control participant harbored a very large repeat length of approximately 2000 repeats.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the unrelated cohort, we also identified CTG18.1 expansion, defined as ≥40 repeats, in 7.7% (95% CI, 4%–11%) of 235 control subjects (≥50 years old), consistent with previous reports in US and European cohorts, 33 but higher than that in studies of Asian cohorts. 12 As a group, our CTG18.1exp+ control subjects did not have repeat lengths significantly different than CTG18.1exp+ FECD patients, so we cannot conclude that CTG18.1exp+ controls have relatively shorter expansions. In fact, one control participant harbored a very large repeat length of approximately 2000 repeats.…”
Section: Discussionmentioning
confidence: 59%
“…The high prevalence of CTG18.1 expansion in this study is comparable to that reported by other studies that have investigated US and European cohorts but is higher than that found by studies of Asian, Indian, and African American US cohorts. 12 The higher frequency of CTG18.1 expansion in certain populations may be the driving mechanism explaining the higher reported prevalence of guttae and the perceived higher incidence of FECD among individuals of northern European and Scandinavian descent, but we are not aware of studies that answer this question using direct epidemiologic comparisons. 29 , 30 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 78% of FECD patients in the United States have an expansion of a CTG repeat sequence in an intron of the TCF4 gene. Traditionally, researchers in the field have generated estimations of repeat length from leukocyte DNA rather than the targeted diseased tissue and have correlated these data with mechanistic changes in affected corneal tissue which includes the role of RNA toxicity, repeat-associated non-AUG translation, and changes in TCF4 expression (see review [ 15 ]). In FECD, technical limitations have previously made it impossible to quantify the TCF4 TNR expansion length in corneal endothelial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Both the FECD and PPCD are genetically heterogenous. However, the most common cause of FECD is the expansion of a non-coding repeat element (termed CTG18.1), which is present in up to 80% of patients with FECD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%